Bird Diversity in Asam Kumbang Crocodile Breeding Area Medan Selayang District Medan City - Erni Jumilawaty (Talenta Publisher, 2021)
Asam Kumbang Crocodile Breeding is a breedig ground for crocodiles that contain several birds. Species diversity is indicated by differences in the types of organisms. One of the most diverse organisms of its kind is birds. Birds in this region are able to setle down and coexist with crocodiles. Crocodiles are one of the predators of bird. It aims to identify the diversity of birds and status of protected birds at the research site. The method used in this study were point count method, thus resulted in 12 species of birds belonging to 5 ordo, 6 family, and 11 genus. The most common birds species found on the 3rd observation with as many as 9 species of birds, while the least species of birds found on the 4th observationas many as 5 species of birds. Diversity index value (H’) of bird in location classified into category of “moderate category” with the results of analysis 1,171 and the indeks equitabilitas value of 0,47. According to the Ministry of Environment and Forestry Regulation 2018, there are 2 types of birds found in the study area of birds found in the study site.